2023
DOI: 10.3390/pathogens12081049
|View full text |Cite
|
Sign up to set email alerts
|

Taurine, a Component of the Tear Film, Exacerbates the Pathogenic Mechanisms of Acanthamoeba castellanii in the Ex Vivo Amoebic Keratitis Model

Lizbeth Salazar-Villatoro,
Bibiana Chávez-Munguía,
Celia Esther Guevara-Estrada
et al.

Abstract: Acanthamoeba spp. is the etiological agent of amoebic keratitis. In this study, the effect of taurine in physiological concentrations in tears (195 μM) on trophozoites of Acanthamoeba castellanii through the ex vivo amoebic keratitis model was evaluated. Trophozoites were coincubated with the Syrian golden hamster cornea (Mesocricetus auratus) for 3 and 6 h. Group 1: Control (−). Corneas coincubated with amoebic culture medium and taurine. Group 2: Control (+). Corneas coincubated with trophozoites without tau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…In this sense, Omaña-Molina et al, (2013) demonstrated that A. castellanii and A. polyphaga invasion and disruption of corneal epithelium in the hamster model is performed by the penetration of the amoebae through cell junctions either by the action of proteases and/or a mechanical effect exerted by trophozoites, suggesting that the contact-dependent activity is an important pathogenic mechanism of these strains of Acanthamoeba [12]. Moreover, in a previous study Omaña-Molina et al, (2010) cocultivated A. castellanii trophozoites with human corneas and reported mechanisms of pathogenicity of amoebic infections were very similar to the previous study using a hamster model and our ndings using a mouse model, which validate these animal models for the study of the pathogenesis of AK [11,13,31].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this sense, Omaña-Molina et al, (2013) demonstrated that A. castellanii and A. polyphaga invasion and disruption of corneal epithelium in the hamster model is performed by the penetration of the amoebae through cell junctions either by the action of proteases and/or a mechanical effect exerted by trophozoites, suggesting that the contact-dependent activity is an important pathogenic mechanism of these strains of Acanthamoeba [12]. Moreover, in a previous study Omaña-Molina et al, (2010) cocultivated A. castellanii trophozoites with human corneas and reported mechanisms of pathogenicity of amoebic infections were very similar to the previous study using a hamster model and our ndings using a mouse model, which validate these animal models for the study of the pathogenesis of AK [11,13,31].…”
Section: Discussionsupporting
confidence: 89%
“…A total of 12 pathogen-free male BALB/c (Mus musculus) mice were used, with an average age of 21 to 28 days and an average body weight of 35 g. Experiments were based on protocol previously described in hamster cornea (Mesocricetus auratus) [11][12][13], and were approved by Research Ethics and Animal Welfare Committee of the University of La Laguna, included in the project known as Evaluation of the in vivo amoebicidal activity of eye drops containing active ingredients administered via the ocular route, with the reference number CEIBA2021-3074.…”
Section: Ex Vivo Infectionmentioning
confidence: 99%
See 1 more Smart Citation